Multiple glassy dynamics in dipole functionalized triphenylene-based discotic liquid crystals revealed by broadband dielectric spectroscopy and advanced calorimetry – assessment of the molecular origin. Issue 33 (8th August 2019) - Yildirim, Arda; Bühlmeyer, Andrea; Hayashi, Shunsuke; Haenle, Johannes Christian; Sentker, Kathrin; Krause, Christina; Huber, Patrick; Laschat, Sabine; Schönhals, Andreas
Abstract : A selected series of dipole functionalized triphenylene-based discotic liquid crystals (DLCs) was synthesized and investigated in a systematic way to reveal the phase behavior and molecular dynamics. Abstract : A selected series of dipole functionalized triphenylene-based discotic liquid crystals (DLCs) was synthesized and investigated in a systematic way to reveal the phase behavior and molecular dynamics. The later point is of particular importance to understand the charge transport in such systems which is the key property for their applications such as organic field-effect transistors, solar cells or as nanowires in molecular electronics, and also to tune the properties of DLCs. The mesomorphic properties were studied by polarizing optical microscopy, X-ray diffraction, and differential scanning calorimetry, which were compared to the corresponding unfunctionalized DLC. The molecular dynamics were investigated by a combination of state-of-the-art broadband dielectric spectroscopy (BDS) and advanced calorimetry such as fast scanning calorimetry (FSC) and specific heat spectroscopy (SHS). Besides localized fluctuations, surprisingly multiple glassy dynamics were detected for all materials for the first time. Glassy dynamics were proven for both processes unambiguously due to the extraordinary broad frequency range covered. The α1 -process is attributed to fluctuations of the alky chains in the intercolumnar space because a polyethylene-like glassy dynamics is observed. This corresponds to a glass transition in a confined three-dimensional space. The α2 -process found at temperatures lower than α1 -process, is assigned to small scale rotational and/or translational in plane fluctuations of the triphenylene core inside distorted columns. This can be considered as a glass transition in a one-dimensional fluid. Therefore, obtained results are of general importance to understand the glass transition, which is an unsolved problem of condensed matter science.